(3eSfO CHj MfjaI GdEeGes - (3GdNhGQRej, eMeO Hf eMehO Hf eMeO, J (B665 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; (B: (3jbhd eMeO Hf eMehO GdNhGQRej GdMeO ddg GdPj SbGfG HWhdg ef CUai TQGjY GdTQGjY hcSGfG HaVdg ef CUai GdeOGQY hCWdY OQGQj TQGjYfG ef CTQa GdeWGdY hgh eWdY SjO GdCUajGA hNGJe GdCfHjGA hTajY GdCee jhe GdLRGAs
(3BNQgG (B:s
(3CNQLg GdMGaX YHO Gddg Hf eMeO Hf CHj GdYhGe hMOKfj CjVG CMeO Hf CHj GdbGSe Yf ESMGb Hf ESQGFjd bGd (B" (3KfG (B" (3YGHO Hf MHjH Hf GMeO bGd MOKfG CHh MfjaI QVj Gddg JYGdi Yfg Je GdLRA GdChd ef eSGfjO CHj MfjaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3JGL GdJQGLe U (B236s
(3eYLe GdeDdajf (B3 / 706s
(3cTa GdXfhf (B2 / 1680s
(3TPQGJ GdPgH (B7 / 104s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs